2022
DOI: 10.1021/acs.est.1c08065
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Transformation Mechanisms of Atmospheric Particulate Bound Mercury Revealed by Mercury Stable Isotopes

Abstract: This study examined the isotopic composition of particulate bound mercury (PBM) in 10 Chinese megacities and explored the associated sources and transformation mechanisms. PBM in these cities was characterized by negative δ202Hg (mean: −2.00 to −0.78‰), slightly negative to highly positive Δ199Hg (mean: −0.04 to 0.47‰), and slightly positive Δ200Hg (mean: 0.02 to 0.06‰) values. The positive PBM Δ199Hg signatures were likely caused by physiochemical reactions in aerosols. The Δ199Hg/Δ201Hg ratio varied from 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 79 publications
2
26
0
Order By: Relevance
“…Most physical and chemical processes lead to MDF, but odd-MIF is mainly produced by photochemical reactions (e.g. photoreduction of aqueous Hg­(II), photodemethylation of methylmercury). Even-MIF is mainly observed in atmospheric samples, and its mechanism may be attributed to atmospheric redox processes. Previous studies have reported Hg isotopes of PBM in different regions (e.g., urban, rural, and coastal areas) , and seasonal even diurnal variation of odd-MIF ,, and indicate that the isotopic compositions of PBM emitted from primary sources would be modified during atmospheric transformation or transportation. However, the mechanism that drives Hg isotope variations of PBM is still poorly understood, especially during the transformations of PBM in severe haze events.…”
Section: Introductionmentioning
confidence: 99%
“…Most physical and chemical processes lead to MDF, but odd-MIF is mainly produced by photochemical reactions (e.g. photoreduction of aqueous Hg­(II), photodemethylation of methylmercury). Even-MIF is mainly observed in atmospheric samples, and its mechanism may be attributed to atmospheric redox processes. Previous studies have reported Hg isotopes of PBM in different regions (e.g., urban, rural, and coastal areas) , and seasonal even diurnal variation of odd-MIF ,, and indicate that the isotopic compositions of PBM emitted from primary sources would be modified during atmospheric transformation or transportation. However, the mechanism that drives Hg isotope variations of PBM is still poorly understood, especially during the transformations of PBM in severe haze events.…”
Section: Introductionmentioning
confidence: 99%
“…3h, i ), in which terrestrial Hg inputs are limited, provide a promising reservoir for tracking atmospheric fluxes of Hg 23 . For the pelagic Gujo-Hachiman section, the negative or near-zero Δ 199 Hg values associated with Hg concentration peaks near the LPME, document elevated fluxes of isotopically light Hg because Δ 199 Hg becomes more positive during atmospheric transport 24 . Combustion of terrestrial organic-rich sediments (e.g., coal 27 ), which can lead to elevated Hg concentrations 28 with a negative MIF in marine deposits 29 , was the likely dominant source of Hg at a global scale 14 (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…1 ). These positive excursions were likely due to photoreduction of Hg(II) during long-distance transport through the atmosphere 24 . Moreover, the sharp decrease of pyrite sulfur isotope (δ 34 S) values coinciding with the extinction interval in the Bunnerong core provides evidence for increasing atmospheric sulfate concentrations, which have been previously linked to aerosol production by the STLIP 32 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Before PBM samples were collected onto the filters, multiple atmospheric processes [e.g., oxidation of GEM to GOM followed by adsorption onto particulates, direct uptake of GEM, and photoreduction of Hg(II) in particulates] might occur and alter the isotope compositions of initial PBM sourced from anthropogenic emissions. 67 These processes could produce significant MIF, but their net effect typically imparts the collected PBM with positive odd-MIF values and Δ 199 Hg/Δ 201 Hg slopes of ∼1.0 [diagnostic of the magnetic isotope effect (MIE)] but sometimes up to 1.6 [diagnostic of the nuclear volume effect (NVE)]. 67 In addition, significant correlations of Δ 200 Hg versus Δ 199 Hg and Δ 204 Hg versus Δ 200 Hg were also typically observed in atmospheric samples (Figures 3D−F and 4D−F).…”
Section: Comparison With the Global Atmospheric Hgmentioning
confidence: 99%